If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25 + 6x = 2x + 27 Reorder the terms: -25 + 6x = 27 + 2x Solving -25 + 6x = 27 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -25 + 6x + -2x = 27 + 2x + -2x Combine like terms: 6x + -2x = 4x -25 + 4x = 27 + 2x + -2x Combine like terms: 2x + -2x = 0 -25 + 4x = 27 + 0 -25 + 4x = 27 Add '25' to each side of the equation. -25 + 25 + 4x = 27 + 25 Combine like terms: -25 + 25 = 0 0 + 4x = 27 + 25 4x = 27 + 25 Combine like terms: 27 + 25 = 52 4x = 52 Divide each side by '4'. x = 13 Simplifying x = 13
| -16-6(30)=-2(8(30)-7) | | 19y-4x=2 | | b=15-(-15) | | 5a^2+3a-8=0 | | -5=10(x-2)+8x | | 6x-2(x+6)=4(x+1)+6 | | 3(4-3a)+7a=18 | | 19x-4y=2 | | 6(3x-2)-(-15x+33)=-12 | | 8-3a+5a^2=0 | | s=2r+3x | | -62=-2(1+56) | | -36+6y=9y | | -2-16=g | | 222=35-x | | -20+2x=-6x+28 | | 3x-5+y=2y-4 | | v=x*y*z | | 39*x=13 | | 7.5(x+3)=25 | | 2x-2=12+-42 | | 4=x/5+x/4 | | x^2-10-x=0 | | V+5v=0 | | 4-6(x+2)=2(x-5)+2 | | 6cos^2(t)+5cos(t)+1=0 | | 3(y+2)-2y=-1 | | 29-13=4(x-6) | | 4x^2+3x-j=0 | | 234=31x-x^2 | | 5x-12=4x+3 | | 5x+3=413 |